Survey of traditional cattle production systems and preferred cattle functions in North and South Wollo Zones, Ethiopia - Tadesse, D.; Ayalew, W.; Hegde, B.P. (2005)
A survey was conducted to characterize cattle production systems and preferred cattle functions in North and South Wollo Zones of the Amhara Regional State of northeastern Ethiopia. Rapid survey and semi-structured questionnaires were used to collect data on herd structures, indicative productive and reproductive performances, preferred cattle functions and trait preferences of cattle. Individual cattle herd sizes ranged from 1 to 24 with site average herd size ranged from 5.5 to 14.0. The number of adult breeding bulls in each herd gave a ratio of one bull to less than three breeding females, and yet breeding bulls are not adequately available in the villages. Based on reported indicative performances, overall average age at first calving in the study area was about 4 years. Similarly average calving intervals ranged between 14.4 and 19.3 months with overall average of 17.6 months. The overall reported average daily milk yield was 1.9 liters with village averages ranging from 1.6 to 2.3 liters. The average reported lifetime calf production was 6.5 during a productive lifetime of about 8 and 10 years for male and female animals, respectively. Generally, cattle are preferred and expected to have multiple production and service functions. The indigenous cattle are preferred to exotic/introduced animals for their robust adaptive attributes. Subsistence smallholder animals do select particularly female breeding animals for a range of desirable attributes of their animals, but some of these attributes are related to behaviour and body form of the animals, which are not necessarily directly related to production functions. Over 91% of the respondents practiced natural, unplanned and uncontrolled mating system.